2008
DOI: 10.1007/s00468-008-0245-4
|View full text |Cite
|
Sign up to set email alerts
|

From desert to cloud forest: the non-trivial phenotypic variation of Canary Island pine needles

Abstract: Pine needles reflect some of the most outstanding xeromorphic characteristics of sclerophyllous plants. Detailed descriptive studies about their anatomy and morphology were carried out since the beginning of the past century but the role the different tissues play in adaptation to diverse environments is still little known. In this work we analyzed morphological and anatomical needle traits of seventeen natural populations of Pinus canariensis Chr. Sm. Ex DC to identify adaptive traits related to drought resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…On the contrary, relative area of the vascular bundle, with chiefly a conductive function, the endodermis, which controls the transport of transpiration water for xylem to stomata (Scholz and Bauch 1973) and traits related to size are negatively related, agreeing with the general tendency of reducing needle dimensions as a consequence of environmental stress (Richardson and Rundel 1998). These correlations would confirm a relevant role of the transfusion tissue in drought adaptation of this species as previously proposed (López et al 2008). However, results do not support that ontogenetic delay is caused by the cost of leaf sclerophylly in this species.…”
Section: Intraspecific Differences In Phenotypic Plasticitysupporting
confidence: 84%
See 1 more Smart Citation
“…On the contrary, relative area of the vascular bundle, with chiefly a conductive function, the endodermis, which controls the transport of transpiration water for xylem to stomata (Scholz and Bauch 1973) and traits related to size are negatively related, agreeing with the general tendency of reducing needle dimensions as a consequence of environmental stress (Richardson and Rundel 1998). These correlations would confirm a relevant role of the transfusion tissue in drought adaptation of this species as previously proposed (López et al 2008). However, results do not support that ontogenetic delay is caused by the cost of leaf sclerophylly in this species.…”
Section: Intraspecific Differences In Phenotypic Plasticitysupporting
confidence: 84%
“…Geographical variation in survival (López et al 2007), ontogeny and traits related to fire response (Climent et al 2004) of this species have been already assessed. Furthermore, in a previous study, we observed distinct needle anatomy and morphology in natural populations of Canary Island pine spread throughout the ecological range of the species (López et al 2008). However, in the mentioned work sampling was done in natural populations, therefore it was not possible to separate environmental and genetic factors eliciting phenotypic variation.…”
Section: Introductionmentioning
confidence: 91%
“…The endodermis plus stele area was the variable most affected by provenance. The transfusion tissue, located in the stele, functions as storage for water and reserve metabolites (Canny 1993) and the larger area of this tissue in the Southern region, in conjunction with the larger mesophyll area, could help to maintain high photosynthetic levels in trees capable of sustaining reduced aerial biomass, which must make use of limited periods favorable for growth in environments subjected to extended periods of water stress (López et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…3). The reduction of needle length helps to conserve water by reducing the transpiring area, and has been previously identified as an important trait conferring drought tolerance in pines (López et al 2008;Dobbertin and Eilmann 2010). Thereby it contributes to the decrease of transpiring area by reduced number and length of shoots (see above).…”
Section: Accepted Articlementioning
confidence: 93%